Factors influencing clinicians' willingness to use an AI-based clinical decision support system - Choudhury, Avishek (Frontiers in Digital Health, 2022)
Background: Given the opportunities created by artificial intelligence (AI) based decision support systems in healthcare, the vital question is whether clinicians are willing to use this technology as an integral part of clinical workflow. Purpose: This study leverages validated questions to formulate an online survey and consequently explore cognitive human factors influencing clinicians’ intention to use an AI-based Blood Utilization Calculator (BUC), an AI system embedded in the electronic health record that delivers data-driven personalized recommendations for the number of packed red blood cells to transfuse for a given patient. Method: A purposeful sampling strategy was used to exclusively include BUC users who are clinicians in a university hospital in Wisconsin. We recruited 119 BUC users who completed the entire survey. We leveraged structural equation modeling to capture the direct and indirect effects of ’AI Perception’ and ’Expectancy’ on clinicians’ Intention to use the technology when mediated by ’Perceived Risk’. Results: The findings indicate a significant negative relationship concerning the direct impact of AI’s perception on BUC Risk (ß= -0.23, p<0.001). Similarly, Expectancy had a negative effect on Risk (ß= -0.49, p<0.001). We also noted a negative impact of Risk on the Intent to use BUC (ß= -0.34, p<0.001). Regarding the indirect effect of Expectancy on the Intent to Use BUC, the findings show a positive impact mediated by Risk (ß= 0.17, p=0.004). The study noted a positive and indirect effect of AI Perception on the Intent to Use BUC when mediated by risk (ß= 0.08, p=0.027). Overall, this study demonstrated the influences of expectancy, perceived risk, and perception of AI on clinicians’ intent to use BUC (an AI system). Conclusion: Identifying the factors determining clinicians’ intent to use AI-based decision support systems can help improve technology adoption and use in the healthcare domain. Enhanced and safe adoption of AI can uplift the overall care process and help standardize clinical decisions and procedures. An improved AI adoption in healthcare will help clinicians share their everyday clinical workload and make critical decisions.